Risk of symptomatic COVID‐19 due to aircraft transmission: a retrospective cohort study of contact‐traced flights during England's containment phase. Issue 3 (1st March 2021) - Blomquist, Paula Bianca; Bolt, Hikaru; Packer, Simon; Schaefer, Ulf; Platt, Steven; Dabrera, Gavin; Gobin, Maya; Oliver, Isabel
Abstract: Background: Knowledge gaps remain regarding SARS‐CoV‐2 transmission on flights. We conducted a retrospective cohort study to estimate risk of acquiring symptomatic SARS‐CoV‐2 on aircraft, to inform contact tracing and infection control efforts. Methods: We identified co‐passengers of infectious passengers on 18 England‐bound flights from European cities up to 12/03/2020, using manifests received for contact tracing. Infectious passengers were laboratory‐confirmed cases with symptom onset from 7 days before to 2 days after the flight. Possible aircraft‐acquired cases were laboratory‐confirmed with onset 3‐14 days post‐flight with no known non‐flight exposure. Manifests was merged with the national case management dataset (identifying cases, onset dates, contact tracing status) and the national COVID‐19 linelist. Contact tracing notes were reviewed to identify non‐flight exposures. We calculated attack rates (ARs) among all co‐passengers and within subgroups, including by distance from infectious cases and number of infectious cases on‐board. Results: There were 55 infectious passengers and 2313 co‐passengers, including 2221 flight‐only contacts. Five possible aircraft‐acquired cases were identified; ARs of 0.2% (95%CI 0.1‐0.5) among all flight‐only contacts and 3.8% (95%CI 1.3‐10.6) among contact‐traced flight‐only contacts sat within a two‐seat radius. The AR among 92 co‐travellers with known non‐flight exposure to infectious cases was 13.0% (95%CI 7.6%‐21.4%). There were insufficient numbers to assess differences between subgroups. Conclusion: We conclude that risk of symptomatic COVID‐19 due to transmission on short to medium‐haul flights is low, and recommend prioritising contact‐tracing of close contacts and co‐travellers where resources are limited. Further research on risk on aircraft is encouraged.